Silent period. Issue 3 (March 2016) - Kofler, M.
Abstract : The cutaneous silent period (CSP) is a transient inhibition of ongoing electromyographic activity in hand muscles elicited by high-intensity electrical fingertip stimulation. Its underlying biologic function seems to be a protective reaction to nociceptive stimuli. The reflex pathway is composed of thin-myelinated A-delta afferents, spinal centromedullary circuitry, and thick-myelinated I-a motor efferents. Thus, evaluation of CSP may be employed to detect A-delta dysfunction in patients with axonal or demyelinating polyneuropathy. Data reviewed from the literature indicate that CSP presence, CSP duration, and CSP latencies are differentially affected by small- and large-diameter afferent and efferent fibers. Presence and number of A-delta axons seem to define CSP presence and duration, whereas CSP latencies depend on conduction properties of A-delta fibers; CSP onset latency is further "fine-tuned" by conduction function of motoneurons. CSP parameters do not differentiate between patients with and without neuropathic pain, concurring with the notion that neuropathic pain is not due to mere A-delta fiber loss.